Assoc. Prof. PhD - Georgian Badicu (PUBLIC LIBRARY SCIENCE1160 BATTERY STREET, STE 100, SAN FRANCISCO, CA 94111, 2025)
Background Childhood obesity poses a significant public health challenge, yet effective school-based physical activity (PA) interventions remain scarce, especially in Pakistan. There is a lack of data assessing the impact of such interventions on obesity and related health outcomes in Pakistani school children. Methods This study aimed to design and implement a school-based intervention targeting multiple levels of the socio-ecological model to increase physical activity and reduce the prevalence of overweight and obesity in Pakistani youth. Conducted from October 2022 to January 2023 in Lahore, Pakistan, the 12-week, non-randomized controlled trial involved 1,200 students from eight schools, with four schools (n=570) in the intervention group and four (n=630) in the control group. Primary outcomes included changes in body mass index (BMI), waist circumference, and the prevalence of overweight/ obesity, measured through anthropometric assessments. Secondary outcomes involved alterations in moderate-to-vigorous physical activity duration. Descriptive statistics, Chisquare tests, general linear mixed models, and repeated measures ANOVA were used for analysis. Results The intervention showed significant improvements across various socio-ecological levels. Intrapersonal factors saw a reduction in fast food consumption from 11.9% to 7.9% (F(1,1198)=90.39, p<0.001; η²=0.074) and an increase in physical activity frequency from 11.9% to 39.6% (F(1,1198)=465.25, p<0.001; η²=0.028). Screen time decreased from 27.0% to 7.4% (F(1,1198)=219.83, p=0.015; η²=0.15), and normal sleep duration increased from 44.6% to 71.8% (F(1,1198)=242.73, p<0.001; η²=0.16). At the interpersonal level, parental involvement in encouraging sports and providing financial support for sports activities significantly increased. School-level factors also showed positive changes, including improved sports facilities and equipment access. Community-level factors revealed increased opportunities for physical activity and a more supportive community environment. The intervention group’s BMI change (−0.06±0.07 kg·m²) significantly differed from the control group’s (0.19±0.09 kg·m²). Conclusions This study demonstrates the effectiveness of a multi-level intervention in boosting physical activity and addressing obesity among Pakistani school-aged children, supporting the implementation of similar school-based interventions.